Predictive value of the ACS NSQIP calculator for head and neck reconstruction free tissue transfer. (30th July 2019) - Tierney, William; Shah, Janki; Clancy, Kate; Lee, Maxwell Y.; Ciolek, Peter J.; Fritz, Michael A.; Lamarre, Eric D.
Abstract : Background: Predictive models to forecast the likelihood of specific outcomes after surgical intervention allow informed shared decision‐making by surgeons and patients. Previous studies have suggested that existing general surgical risk calculators poorly forecast head and neck surgical outcomes. However, no large study has addressed this question while subdividing subjects by surgery performed. Objectives: To determine the accuracy of the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) Surgical Risk Calculator in estimating length of hospital stay and risk of postoperative complications after free tissue transfer surgery. Study Design: A retrospective chart review of patients at one institution was performed using Current Procedural Terminology codes for anterolateral thigh (ALT) flap, fibula free flap (FFF), and radial forearm free flap (RFFF) reconstruction. Output data from the ACS NSQIP surgical risk calculator were compared with the observed rates in our patients. Methods: Incidences of cardiac complications, pneumonia, venous thromboembolism, return to the operating room, and discharge to skilled nursing facility (SNF) were compared to predicted incidences. Length of stay was also compared to the predicted length of stay. Results: Three hundred thirty‐six free flap reconstructions with 197 ALT flaps, 85 RFFFs, and 54 FFFFs were included. Brier scores were calculated using ACS NSQIP forecast and actual incidences. No Brier score was <0.01 for the entire sample or any subgroup, which indicates that the NSQIP risk calculator does not accurately forecast outcomes after free tissue reconstruction. Conclusion: The ACS NSQIP failed to accurately forecast postoperative outcomes after head and neck free flap reconstruction for the entire sample or subgroup analyses. Level of Evidence: 4 Laryngoscope, 130:679–684, 2020